"We are the Jews of today": Filipino domestic workers in Israel and the language of diaspora - Liebelt, Claudia (Hagar: Studies in Society and Culture, 2008)
While the Jewish diaspora is generally treated as the ideal type of an imagined global community, the notion of a Filipino labor migrant diaspora has arisen more recently. As I will show, the analysis of "diaspora" as an emic discourse offers much insight into the political and affective aspects of economic, social and cultural dislocation within a global capitalist order. Based on ethnographic research on Filipino domestic workers in Israel, this article focuses on migrants' usage of the language of diaspora, rather than discussing whether their historical experiences justify their description as such. By declaring to Israeli policymakers and employers that "We are the Jews of today," Filipino domestic workers in Israel are not only demonstrating their knowledge of and solidarity with Jewish history and suffering, but-against the background of a migration regime that rigidly excludes non-Jews-negotiate rights and belonging by appeals to pity and compassion, hereby claiming political inclusion.